Lymphomatoid Papulosis Type A: A Case Report of the "Wait-and-See Strategy" in a 27-Year-Old Male Patient with Extensive Disease. (16th July 2019) - Kavvalou, Eirini; Stefanidou, Maria; Krueger-Krasagakis, Sabine Elke; Evangelou, George; Koumaki, Dimitra; Marinos, Leonidas; Tzardi, Maria; Krasagakis, Konstantinos
Abstract : This is the case of a 27-year-old male patient with a newly diagnosed extensive lymphomatoid papulosis type A involving cosmetically sensitive areas (e.g. face), who refused to be treated with a low dose of methotrexate, as recommended by the published literature. The natural course of the disease was proved to be strikingly satisfying though, with a complete regression of all skin lesions at the 4-week follow-up, including an ulcerated nodule 3 x 3 cm in dimension, which was expected to heal at least in months. We report this case to reconsider weighting the risks and the short-term benefits of methotrexate treatment, even in the case of an extensive disease.